Pyo-septic complications of severe necrotizing forms of acute pancreatitis - N. N. Veligotsky; S. E. Arutyunov; M. V. Klymenko; K. A. Aleksanyan (Сучасні медичні технології)
Purpose of the study. Develop an algorithm for the diagnosis and treatment of purulent-septic complications of severe necrotizing forms of acute pancreatitis.